a) (x-1)(x+2) =-13
b) (3x-2)(2x+1)=31
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(\Leftrightarrow6x^2-2x=6x^2-13\)
=>-2x=-13
hay x=13/2
b: \(\dfrac{x}{3}-\dfrac{2x+1}{6}=\dfrac{x}{6}-x\)
=>2x-2x-1=x-6x
=>-5x=-1
hay x=1/5
c: \(\Leftrightarrow\left(x+1\right)^2-\left(x-1\right)^2=x^2+3\)
\(\Leftrightarrow x^2+3-x^2-2x-1+x^2-2x-1=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-3\right)=0\)
=>x=3
Câu 1:
a) Ta có: x-3 là ước của 13
\(\Leftrightarrow x-3\inƯ\left(13\right)\)
\(\Leftrightarrow x-3\in\left\{1;-1;13;-13\right\}\)
hay \(x\in\left\{4;2;16;-10\right\}\)(thỏa mãn)
Vậy: \(x\in\left\{4;2;16;-10\right\}\)
b) Ta có: \(x^2-7\) là ước của \(x^2+2\)
\(\Leftrightarrow x^2+2⋮x^2-7\)
\(\Leftrightarrow x^2-7+9⋮x^2-7\)
mà \(x^2-7⋮x^2-7\)
nên \(9⋮x^2-7\)
\(\Leftrightarrow x^2-7\inƯ\left(9\right)\)
\(\Leftrightarrow x^2-7\in\left\{1;-1;3;-3;9;-9\right\}\)
mà \(x^2-7\ge-7\forall x\)
nên \(x^2-7\in\left\{1;-1;3;-3;9\right\}\)
\(\Leftrightarrow x^2\in\left\{8;6;10;4;16\right\}\)
\(\Leftrightarrow x\in\left\{2\sqrt{2};-2\sqrt{2};-\sqrt{6};\sqrt{6};\sqrt{10};-\sqrt{10};2;-2;4;-4\right\}\)
mà \(x\in Z\)
nên \(x\in\left\{2;-2;4;-4\right\}\)
Vậy: \(x\in\left\{2;-2;4;-4\right\}\)
Câu 2:
a) Ta có: \(2\left(x-3\right)-3\left(x-5\right)=4\left(3-x\right)-18\)
\(\Leftrightarrow2x-6-3x+15=12-4x-18\)
\(\Leftrightarrow-x+9+4x+6=0\)
\(\Leftrightarrow3x+15=0\)
\(\Leftrightarrow3x=-15\)
hay x=-5
Vậy: x=-5
c: \(\dfrac{x-2}{x-1}=\dfrac{x+4}{x+7}\)
=>(x-2)(x+7)=(x+4)(x-1)
\(\Leftrightarrow x^2+5x-35=x^2+3x-4\)
=>5x-35=3x-4
=>2x=31
hay x=31/2
h: \(\dfrac{3x+2}{5x+7}=\dfrac{3x-1}{5x-3}\)
\(\Leftrightarrow\left(3x+2\right)\left(5x-3\right)=\left(3x-1\right)\left(5x+7\right)\)
\(\Leftrightarrow15x^2-9x+10x-6=15x^2+21x-5x-7\)
=>x-6=16x-7
=>-15x=-1
hay x=1/15